Attention Deficits in Stroke Patients: The Role of Lesion Characteristics, Time from Stroke, and Concomitant Neuropsychological Deficits - Spaccavento, Simona (Behav Neurol, 2019)
Attention impairments are frequent in stroke patients with important consequences on the rehabilitation outcomes and quality of life. The aim of the study was to perform a comprehensive assessment of selective and intensive attention processes in a large population of brain-damaged patients, evaluating the influence of the side and site of the brain lesion, the time from stroke, and the concomitant presence of aphasia or neglect. We assessed 204 patients with a first unilateral brain lesion and 42 healthy individuals with three subtests of the Test of Attentional Performance (TAP): Alertness, Go-No Go, and Divided Attention. 44.4% of patients had an impairment in both intensive and selective aspects of attention, 5.6% had deficits only in the intensive component, and 31.8% had deficits only in selective tasks. More than 80% of the patients fell below the cut-off point on at least one task. Patients with a right hemispheric lesion (RHL) were more impaired than patients with a left hemispheric lesion (LHL) especially in tonic and phasic alertness. Patients with total anterior infarcts (TACI) presented the worst profile compared to other stroke subtypes, with a difference between total and lacunar subtypes in the Alertness test, independent of the presence of warning. Patients in the chronic phase had shorter RTs than acute patients only in the Alertness test. In patients with LHL, the presence of aphasia was associated with a greater deficit in selective attention. In patients with RHL, the presence of unilateral neglect was associated with impaired alertness and selective attention. Attention deficits are common after a unilateral first stroke. In keeping with the hierarchical organization of attention functions, results confirm the important role of the right hemisphere for the intensive components of attention, also highlighting the involvement of left hemisphere functioning for the selective aspects, possibly indicating a role of its linguistic functions.